Hysteresis in Labor Markets? : Evidence from Professional Long-Term Forecasts - Bluedorn, John (IMF Working Papers; Working Paper, 2019)
We explore the long-term impact of economic booms on labor market outcomes using a novel approach based on revisions to professional forecasts over the past 30 years for 34 advanced economies. We find that when employment rises unexpectedly, forecasters typically raise their long-term forecasts of employment by more than one-for-one and also expect a strong rise in labor force participation, suggesting more persistent effects than is traditionally assumed. Economic booms associated with changes in aggregate demand, when inflation is rising and unemployment falling unexpectedly, also come with persistent long-term effects on expected employment and labor force participation, suggesting positive hysteresis. Our forecast evaluation tests indicate that forecasters are, on average, unbiased in their assessment of these positive, persistent effects.